Formulation and Characterization of Microencapsules Containing Ethanol Extract of Sungkai Leaves (Peronema canescens Jack) - Tarigan, Indra Lasmana; Farah, Farah; Puspitasari, Ratih Dyah; Saharin, Siti Munirah; Latief, Madyawati (Department of Chemistry, Faculty of Science and Technology Universitas Jambi, 2025)
The Sungkai plant (Peronema canescens Jack) is a widely recognized medicinal plant in Indonesia, with its leaves recently gaining attention for their potential health benefits. This study explores the microencapsulation of ethanol extract from Sungkai leaves using three different coating materials—maltodextrin, inulin, and Arabic gum—at varying concentrations. The aim of this study was to identify the optimal microencapsulation formulation using these materials. Microencapsulation was performed using the extrusion method, and the best formulation was characterized by evaluating its physicochemical properties, morphology, and infrared (IR) spectrum. Antioxidant activity was measured using the 2,2-diphenyl-1-picrylhydrazyl (DPPH) assay. The results showed that microencapsulant formulation A1 exhibited superior physicochemical properties compared to other formulations. Scanning electron microscopy (SEM) analysis of sample A1 revealed a smooth surface with a slightly rounded shape and minimal wall folds or cracks, suggesting good stability. Fourier-transform infrared (FTIR) analysis confirmed effective encapsulation of the ethanol extract. While the crude extract demonstrated the highest antioxidant activity, microencapsulation slightly reduced this activity. Among the microencapsulated samples, formulation A1 (using Arabic gum) retained the most antioxidant potential. In conclusion, formulation A1, utilizing Arabic gum as the coating material, was found to be the optimal microencapsulation formulation for the ethanol extract of Sungkai leaves.